Tough Gel Electrolyte Using Double Polymer Network Design for the Safe, Stable Cycling of Lithium Metal Anode. (5th January 2018) - Wu, Haiping; Cao, Yue; Su, Haiping; Wang, Chao
Abstract: The growth of lithium dendrites and low coulombic efficiency restrict the development of Li metal anodes. Polymer electrolytes are expected to be promising candidates to solve the issue, but ways to obtain a polymer electrolyte that integrates high ionic conductivity and high mechanical toughness is still challenging. By introducing a double polymer network into the electrolyte design to reshape it, a tough polymer electrolyte was developed with high conductivity, and stable operation of lithium metal anodes was further realized. The double network (DNW) gel electrolyte has high modulus of 44.3 MPa and high fracture energy of 69.5 kJ m −2 . The conductivity of DNW gel is 0.81 mS cm −1 at 30 °C. By using this gel electrolyte design, the lithium metal electrode could be cycled more than 400 times with a coulombic efficiency (CE) as high as 96.3 % with carbonate‐based electrolytes.